2014
DOI: 10.7785/tcrt.2012.500354
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Stereotactic Radiosurgery Treatment Results for Skull Base Chordomas

Abstract: Chordomas are uncommon neoplasms and there is still controversy regarding establishment of diagnosis and management. The aim of this study was to evaluate efficacy and toxicity of fractionated stereotactic radiosurgery (FSRS) in skull base chordomas. There were 4 female (36%) and 7 male (64%) patients. FSRS was delivered with CyberKnife (Accuray Inc., Sunnyvale, CA). The median tumor volume was 14.7 cc (range, 3.9-40.5 cc). The median marginal tumor dose was 30 Gy (range, 20-36 Gy) in a median 5 fractions (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…A limited number of published series evaluate FSRT for chordomas and chondrosarcomas (10, 23, 3133), and our study provides additional evidence regarding the efficacy and toxicity associated with its use. Previous work from the North American Gamma Knife Consortium retrospectively examining single fraction treatment demonstrated a 5-year OS of 80% with an improved 5-year OS of 93% in patients with no prior RT (28), consistent with outcomes observed in our data.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A limited number of published series evaluate FSRT for chordomas and chondrosarcomas (10, 23, 3133), and our study provides additional evidence regarding the efficacy and toxicity associated with its use. Previous work from the North American Gamma Knife Consortium retrospectively examining single fraction treatment demonstrated a 5-year OS of 80% with an improved 5-year OS of 93% in patients with no prior RT (28), consistent with outcomes observed in our data.…”
Section: Discussionmentioning
confidence: 80%
“…Multiple studies have assessed single fraction stereotactic radiosurgery for chordoma and chondrosarcoma management, but FSRT has theoretical advantages compared to single fraction treatment including a lower risk of radiation toxicity in nearby critical structures and the possibility of safely treating larger tumor volumes with multiple fractions (20, 22, 23, 2530). A limited number of published series evaluate FSRT for chordomas and chondrosarcomas (10, 23, 3133), and our study provides additional evidence regarding the efficacy and toxicity associated with its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SRT using Novalis (BrainLAB, Tokyo) was done for recurrence in one case, as the recurrent tumors were relatively large and fractionated SRT was deemed better to avoid adverse radiation effects. A number of papers have been published on chordoma SRS/SRT both with particle-beam and photon-beam [3,[19][20][21][22][23][24][25][26][27][28]. However, in early-reported series the treatment results of both chordoma and chondrosarcoma were mixed [29].…”
Section: Chordomamentioning
confidence: 99%
“…Numerous modern SRS and SFRT series have shown suboptimal outcomes for sbC patients treated with these radiation modalities. [57][58][59] These suboptimal results may be best explained by the stereotactic margins defined during the planning process and radiation dose delivered to these patients. Regarding the former, Snider et al have shown undisputedly the importance of margins for extracranial chordomas.…”
Section: Skull-base Tumoursmentioning
confidence: 99%